2016
DOI: 10.1007/s00262-016-1913-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of pembrolizumab-induced type-1 diabetes mellitus and discussion of immune checkpoint inhibitor-induced type 1 diabetes

Abstract: Immune checkpoint inhibitors such as pembrolizumab, ipilimumab, and nivolumab, now FDA-approved for use in treating several types of cancer, have been associated with immune-related adverse effects. Specifically, the antibodies targeting the programmed-cell death-1 immune checkpoint, pembrolizumab and nivolumab, have been rarely reported to induce the development of type 1 diabetes mellitus. Here we describe a case of a patient who developed antibody-positive type 1 diabetes mellitus following treatment with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 33 publications
2
49
0
2
Order By: Relevance
“…Indeed, the case reported by Chae et al (2017) (Table 4) showed a rapid decrease of serum C-peptide levels (from 0.81 ng/mL at the onset of diabetes mellitus to less than 0.1 ng/mL 14 days later). Further studies are therefore required to clarify whether such cases with positive islet-related autoantibodies and lower HbA1c levels of < 8.7% represent a novel subtype of fulminant type 1 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, the case reported by Chae et al (2017) (Table 4) showed a rapid decrease of serum C-peptide levels (from 0.81 ng/mL at the onset of diabetes mellitus to less than 0.1 ng/mL 14 days later). Further studies are therefore required to clarify whether such cases with positive islet-related autoantibodies and lower HbA1c levels of < 8.7% represent a novel subtype of fulminant type 1 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, twelve cases of anti-PD-1 therapy-induced type 1 diabetes mellitus with positive islet-related autoantibodies (type 1A) have been reported in the literatures (Table 4) (Hughes et al 2015;Martin-Liberal et al 2015;Mellati et al 2015;Hansen et al 2016;Hofmann et al 2016;Lowe et al 2016;Li et al 2017;Araujo et al 2017;Chae et al 2017). Thyroid dysfunction accompanied by positive thyroid autoantibodies occurred in at least three out of these twelve cases of type 1 diabetes mellitus with positive isletrelated autoantibodies.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, the diagnosis itself was relatively easy, and we could manage the acute phase of fulminant T1DM and ketoacidosis with sufficient fluid supply, electrolyte correction, and the administration of insulin. Generally, many irAEs can be managed by discontinuing the ICIs or with the use of steroids; these treatments rarely improve endocrine function in cases of hypothyroidism or T1DM . In this case, we did not use steroids as it was irreversible and the condition was manageable with insulin therapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, some patients can develop severe adverse effects (grade 3 to 5), including diarrhea, colitis, increased alanine aminotransferase levels, interstitial pneumonia and interstitial nephritis [37][38][39] . Anti-PD-1 treatment has also been associated with the development of type 1 diabetes mellitus [40] , hepatitis [41] and the exacerbation of pre-existing autoimmune conditions such as psoriasis [42,43] , among others. It is of note that severe adverse events seem to be more common in melanoma patients treated with anti-CTLA-4 (around 20%) compared to those treated with anti-PD-1 (10%-13%) [37,38] .…”
Section: Treatment-related Adverse Events and Their Managementmentioning
confidence: 99%